Frequency Reconfigurable Monopole Antenna Using Switchable Slotted Triangular Radiators - Fayyadh Ahmed; Bayez Al-Sulaifanie (Engineering and Technology Journal, 2018)
A new configuration of multi-state switchable wideband /multi-narrowband is demonstrated. The proposed antenna is based on a printed rectangular monopole antenna (PRMA) that covers wideband 3.3 GHz WiMAX frequency range. To generate a multi-state switchable antenna, center part of PRMA has been removed without distorting the PRMA behavior. Three PIN diode switches are used to control different operating modes. Eight-operating modes, 2n modes (n is number of switches) are achieved by setting the switches ON or OFF. Initial results were obtained by using short and open circuits instead of implanting PIN diode. The merit of the antenna design is that it allows various groups of its operating frequency bands to be selected using different switches states. Therefore, by selecting different antenna modes, a variety of communication systems can be conveniently served by only one antenna. The designed antenna has a simple planar structure and compact size of 30×50 mm2. Simulation and measured results show that realized gain in all operating bands is varied from -1.1 to 5 dBi. The proposed antenna demonstrates good impedance matching, stable radiation pattern and reasonable gain at all frequency bands. Simulation results have been obtained from commercial CST-2014 Microwave Studio. The antenna is fabricated and tested using R&S ZVL 13 Vector Network Analyzer (VNA). There are accepted results between the prototype and the simulated one.